Comparison of the design and methodology of Phase 3 clinical trials of bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) and dolutegravir-based dual therapy (DTG) in HIV: a systematic review of the literature. Issue 1 (2nd January 2023) - Grau, Santiago; Miró, Jose Maria; Olalla, Julian; Alcalá, Juan C; Castro, Antonio; Rubio-Rodríguez, Dario; Rubio-Terrés, Carlos
ABSTRACT: Introduction: Current recommended antiretroviral regimens include a combination of two (dual; DT) or three (triple; TT) antiretroviral drugs. This study aims to determine whether the quality of evidence from clinical trials of dolutegravir (dolutegravir/lamivudine [DTG/3TC] or dolutegravir/rilpivirine [DTG/RPV]) is methodologically comparable to that of clinical trials conducted with bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF). Areas covered: A systematic review of the medical literature was carried out in PubMed without date or language restrictions, following the PRISMA guidelines. All aspects of the methodological design of phase 3 randomized clinical trials (RCTs) of DT and TT, evaluated by the European Medicines Agency (registration trials), were reviewed. The quality of clinical trials was assessed using the Jadad scale. Expert opinion: The search identified 5, 3 and 2 phase 3 RCTs with BIC/FTC/TAF, DTG/3TC and DTG/RPV, respectively, that met the inclusion criteria. The designs would not be comparable due to differences in pre-randomization losses, blinding, patient recruitment, as well as differences in methodological quality, with the average score of the RCTs conducted with BIC/FTC/TAF, DTG/3TC and DTG/RPV being 4.2 (high quality), 3.0 (medium quality) and 3.0 (medium quality), respectively. Due to methodological differences between the BIC/FTC/TAF, DTG/3TC and DTG/RPV RCTs, the results of these are not comparable.